2019
DOI: 10.1016/j.jesf.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Hong Kong's 2018 report card on physical activity for children and youth

Abstract: Background/objectiveThe Active Healthy Kids 2018 Hong Kong Report Card provides evidence-based assessment across 12 indicators of physical activity behaviors, sleep, and related community and government initiatives for children and youth.MethodsThe systematic development process provided by the Active Healthy Kids Global Alliance was used. The best available data from the past 10 years were reviewed by a panel of experts. According to predefined benchmarks, letter grades were assigned to 12 indicators (Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…The results of the study pointed out that peer group educational intervention increased students' physical activity, while education through lectures did not show a significant effect on the promotion of students' physical activity. Consistent with previously conducted studies, one of the main findings of the present study was the low level of physical activity among the students at the commencement of the study (24)(25)(26).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study pointed out that peer group educational intervention increased students' physical activity, while education through lectures did not show a significant effect on the promotion of students' physical activity. Consistent with previously conducted studies, one of the main findings of the present study was the low level of physical activity among the students at the commencement of the study (24)(25)(26).…”
Section: Discussionsupporting
confidence: 91%
“…The recent Hong Kong 2018 report card on PA for children and youth [28] concluded that children’s low MVPA and high ST were likely affected by their immediate environment, including schools. Having access to activity-enhancing indoor facilities would be advantageous to children with disabilities, especially during summer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented consistent findings in low level of PA among children and youth. 1 , 2 , 3 , 4 , 5 , 6 Four out of five young people worldwide do not meet the recommended PA level of 60 min daily as it is recommended by WHO. 2 , 3 , 7 , 8 , 9 The pandemic of physical inactivity has urged the government of many nations to call up an action by joining a global movement called The Global Matrix Report Card (RC) initiated by Active Healthy Kids Global Alliance (AHKGA).…”
Section: Introductionmentioning
confidence: 99%